Effect of mindfulness-based cognitive therapy vs. psychoeducational intervention on plasma brain-derived neurotrophic factor and cognitive function in bipolar patients: a randomized controlled trial - Carracedo-Sanchidrian, Diego; de Dios-Perrino, Consuelo; Bayon-Perez, Carmen; Rodriguez-Vega, Beatriz; Bravo-Ortiz, Maria-Fe; Ortega, Miguel Á.; González-Pinto, Ana-Maria; Lahera, Guillermo (Frontiers in Psychiatry, 2024)
Few controlled trials have assessed the benefits of Mindfulness Based Cognitive Therapy (MBCT) on cognitive functions and brain-derived neurotrophic factor (BDNF) in bipolar disorder (BD). This study aims to evaluate the impact of MBCT adjunctive treatment on these variables. Main hypothesis was that MBCT would improve cognitive functioning and BDNF more than Psychoeducation and TAU. Randomized, multicenter, prospective and single-blinded trial. Included BD outpatients randomly assigned to three treatment arms: MBCT plus treatment as usual (TAU), Psychoeducation plus Tau and TAU. Cognitive functions were assessed with Continuous Performance Test-